Divine Virtues and Spiritual Conflict: An Exegetical, Patristic, and Contemporary Analysis of Ephesians 6:14–18 - BENEA, Nicolae-Olimpiu (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2024)
This study examines Ephesians 6:14–18 through exegetical, patristic, and contemporary lenses, interpreting Paul’s “armor of God” as divine virtues essential for Christian ethical and spiritual life. Combining rigorous philological analysis with patristic insights from Origen, Chrysostom, Augustine, Gregory of Nyssa, Basil the Great, Cyril of Jerusalem, Theodoret of Cyrus, and Cyprian, the research highlights each virtue—truth, righteousness, peace, faith, salvation, the Word of God, and prayer—as foundational to spiritual resilience. Contemporary contributions by Benjamin L. Merkle, Hans Hübner, Andreas Dettwiler, Gerhard Sellin, Ekaterini Tsalampouni, Ioannis Karavidopoulos, Rainer Kampling, Frank Thielman, Jennifer Strawbridge, and Fredrick J. Long add further theological, rhetorical, and existential depth, emphasizing the ongoing relevance and transformative potential of Paul’s metaphor for today’s Christian communities.